THE ASIA PACIFIC BIOETHICS PROGRAM OF THE UNESCO CHAIR IN BIOETHICSCAN RESEARCH IN DEVELOPING COUNTRIES BE BOTH ETHICAL AND BENEFICIAL TO LOGAL COMMUNITY ? - Theong H. Low (Majalah Kedokteran Andalas, 2014)
Abstractln 2005 at the 33rd Session of General Conference at UNESCO, it adapted the Universaldeclaration on Bioethics and Human Rights. Declaration article 1.1 outlines the principals thatrespond to ethical issue related to medicine, life sciences and associated technologies as appliedto human beings. Thus the international standards for Bioethics are grounded in a language ofrights -to safe guard human dignity and human rights. UNESCO made ethics of Science andtechnology one of its 5 priority areas. lt is charged with promoting the education of ethical issuesof Science and Technology. The UNESCO Program in this area aims to strengthen lhe ethicallink between scientific advancement that is taking place and the Cultural, Legal, Philosophicaland religious context in which it occurs.The disparity of health amongst the world's communitiesis largely determined by the wealth of the countries. Developed countries have access to cleanwaters, vaccines and new medical technologies whereas developing countries do not.Researches in these countries are also funded by the wealthy countries and we will need toprotect these countries from exploitation by those with the means in the name of clinicalresearch.Hence, we have to discuss the necessary conditions for models allowing lnstitutionalReview Boards to grani exceptions in low income countries to circumvent the need for "WorldBest Practices" in their research requirements. There are commentators arguing that "World'sBest Practiees sheuld always be used in ali countries, but financial burden in the developingcouniries prevents this. A total ban cn any research other than the world's best practice wouldprevent exploitation, but this may block important research that can improve health care in thesecountries. So is it possibie to address the potentiai for exploitation while allowing research thathas the potential to benefit the host communities.We argue that lnstitutional Review Boardsshould be allowed to grant exceptions for research on grounds that the research satisfies theScientific Necessity, Relevance for the host communities, sufficient host community benefits andSubject and Host Community nonrnaleficence.The argument has focused on the controversialHIV vertical transmission, and the trials used. World Best Practice is currently the long coursetreatment using AZT (zidovudine), but this is expensive involving early prenatal visits, frequentvisits and lV infusions during labour, which is not feasible nor affordable in these countries.However studies in South Africa has identified that apprcximalely 75% of HIV verticaltransmissions occurs ciuring or after delivery. Hence, trials comparing short ccurse AZTtreatment against placebo were done on ihe grounds that it is better than no treatment at all. Thetrials suggested that short course ti'eatment is possibly better than placebo. Yet the variability inthe transmission rate may suggest that the short-course treatment was not woi-th pur"suing.Theknowledge thal.75% of HIV vertical transmission occurs during delivery has led investigators tothe iandmark trials using nevirapine as a single dose given during labour offerring a feasible andaffordable treatment for reducing the rate of vertical transmission.To justify the relevance of theseissues, the Elizabeth Glaser Paediatrics AIDS Foundation has devoted $100 miilion to preventHIV vertical transmission. Assuming a cost of $250 per mother-child treatment using the longcourse AZT would translate to 65,000 fewer HIV infected child. Yet devoting the same money toa single-dose nevirapine, at $4 per mother-child can translate to 270,000 fever HIV infected child,lffrttE Supplemen Majalah Kedokteran Andalas. Vol. 37. No.Supl.1, [/aret 2014potentially saving an additional 200,000 lives. The UNESCO Chair in Bioethics was establishedto coordinate and stimulate an international network of lnstitutes for Medical Ethics Training. lnthis role there is a need to develop an up to date syllabus for Medical ethics education which willsatisfy requirements of the Medical fraternity. These followed Two lnternational Studies in 2001that UNESCO undertook in researching the importance and quality of education in ethics inMedical Colleges and faculties all over the world. The results confirmed that there is an emergingneed for introduction of teaching of Medical ethics as a consequence of several social andscientific processes that have taken place. These included the relationship between health careproviders and their patients, the choice of medical interventions for the individual patient, thechoice of Public health interventions, the evaluation of effects of health care interventions, thecollaboration between teams engaged in health care activities and the choice of goals andmethods of medical reseai'ch.Hence, research using less than the world's best practice can beethical and has the potential to provide sufficient benefit for the host communities and IRB shouldbe given the authority to approve such activities on a case by case basis.Affiliasi Penulis : Director Centre for Asia Pacific Bioethics Studies, Korespondensi : Theong H. Low, email :thlow@bigpond. net.au,